A study of massive electron pairs and associated particles produced at the CERN ISR - Angelis, A; Basini, G; Besch, H; Breedon, R; Camilleri, L; Chapin, T; Cool, R; Cox, P; Von Gagern, C; Grosso-Pilcher, C; Hanna, D; Humphries, B; et al. (1991)
A sample of 105 e+e- events with an invariant mass greater than 11 GeV/c2 produced is pp collisions at a center-of-mass energy of 62.3 GeV is discussed. Cross sections are presented as a function of mass and transverse momentum. The multiplicity, transverse momentum, and azimuthal dependence of associated particles are also studied.